WACANA NEGARA MARITIM DAN REIMAJINASI NASIONALISME INDONESIA - Paskarina, Caroline (JWP (Jurnal Wacana Politik), 2016)
Although Indonesia is an archipelagic state, but the discourse on maritime state is not yet become the main discourse in the construction of nation and state of Indonesia. This discourse is reemerged when President Joko Widodo make it as one of the main strategic agenda of hisadministration. The re-emerging of this maritime nation discourse is interesting to be studied in terms of nationalism, as an attempt to reconstructing the Indonesian national identity imagination. By tracking the dynamics of the arguments that enliven the discourse in Indonesian politics, this paper wants to uncover why this discourse re-emerged and what is the political interests behind thereimagination of Indonesian nationalism.